Homelessness during the Coronavirus Pandemic. Exploratory Study in Switzerland. Issue 2 (1st February 2023) - Molnar, Lorena; Hashimoto, Yuji Z.
ABSTRACT: The coronavirus pandemic has negatively affected people of all social strata, and continues to do so, but its effect has been the most severe on members of the most precarious populations. In this exploratory study conducted in Switzerland, the specific situation of homeless people, a particularly vulnerable population, is examined from a criminological perspective. In total, we surveyed 32 homeless individuals: 14 during the first wave of the pandemic (March-September 2020) and 18 during the second wave (December 2020-March 2021). Results corroborate that the pandemic has had adverse effects on the respondents – both socioeconomic and psychological. Most of the participants do not use drugs and, overall, those who reported drug use did not report an increase during the epidemic. The occurrence of both victimization and offending is low among the participants. Ethical and methodological considerations such as the minimization of social desirability bias, satisficing, as well as the recruitment of difficult-to-reach participants and data collection more broadly during a pandemic are discussed.